Design of a Web-Based Mosque Cash Management Application - dewi, Ika Parma; Marta, Rizkayeni; Mursyida, Lativa; Sari, Erni Marlina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of applications and information systems is crucial for improving work productivity. The cash management at Al Azhar Mosque is still done manually, recording all incoming and outgoing transactions in a cash book. This method is inefficient and does not help the treasurer to be more productive. Preparing reports requires extensive record-keeping, which is time-consuming and prone to errors. No application allows the Treasurer and Chairman of Al Azhar Mosque to view financial reports of the mosque's cash. A web-based mosque cash application is expected to assist the treasurer in recording and generating financial reports more efficiently. This application is built using the waterfall method as a foundation, utilizing Unified Modeling Language (UML) and programming languages such as PHP, CSS, and JavaScript, supported by a MySQL database. The result of this application is an online-accessible mosque financial report with valid and continuously updated data, such as mosque cash, social cash, cash recaps, and cash reports.